Effects of one year of daily face mask wearing on the skin during the coronavirus disease 2019 pandemic - Park, Sae‐ra; Han, Jiyeon; Yeon, Yeong Min; Kang, Na Young; Kim, Eunjoo; Suh, Byung‐Fhy (Skin research and technology, 2022)
Background As coronavirus disease 2019 (COVID‐19) continues, the long‐term daily use of masks is increasing. A full year includes the four seasons of spring, summer, autumn, and winter. Skin may have been affected by the seasons and further affected by the use of masks. In a previous study, we confirmed the short‐term and 6‐month effects of wearing face masks. In this study, we investigated how certain characteristics of the skin change when wearing a mask for 1 year. Furthermore, we compared skin covered by the mask (mask‐skin zone) to skin that was not covered. Materials and methods The participants were 18 healthy adults (8 men; 10 women) who were asked to wear masks in their daily lives from June 2020 to June 2021. During this period, participants’ skin characteristics, such as trans‐epidermal water loss, skin hydration, skin elasticity, skin keratin amount, skin pore area, skin temperature, skin redness, and skin color, were measured five times. Results Trans‐epidermal water loss, skin keratin amount, skin pore area, skin color, and skin elasticity changed significantly during the year. Furthermore, trans‐epidermal water loss, skin hydration, skin keratin amount, skin pore area, and skin color were significantly different between the mask‐wearing and non‐mask‐wearing areas of the face. Conclusion The skin characteristics of the mask‐skin zone can be affected by long‐term wearing of a face mask under lifestyle and environmental conditions. During the COVID‐19 pandemic, skin care for the mask‐skin zone is also necessary for people who do not wear masks on a daily basis.